2011
DOI: 10.1007/s10557-011-6288-6
|View full text |Cite
|
Sign up to set email alerts
|

Age Related Issues in Reperfusion of Myocardial Infarction

Abstract: Advances in pharmacological treatment and effective early myocardial revascularization have led to improved clinical outcomes in patients with acute myocardial infarction (AMI). However, it has been suggested that compared to younger subjects, elderly AMI patients are less likely to receive evidence-based treatment. Several reasons have been postulated to explain this trend, including uncertainty regarding the benefits of the commonly used interventions in the older age group as well as increased risk associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 72 publications
1
13
0
4
Order By: Relevance
“…1,3,24 Clinically, death following acute myocardial infarction was shown to be more likely in human beings of older age than in young people. 25,26 It was also shown that death due to acute myocardial infarction was encountered more often in males compared to corresponding females before menopause, and was the same after menopause. 27 Drugs such as antihistamines, antibiotics, antimalarials and anti arrhythmic induce the torsades de pointes type of ventricular arrhythmia much more easily in females rather than males.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,24 Clinically, death following acute myocardial infarction was shown to be more likely in human beings of older age than in young people. 25,26 It was also shown that death due to acute myocardial infarction was encountered more often in males compared to corresponding females before menopause, and was the same after menopause. 27 Drugs such as antihistamines, antibiotics, antimalarials and anti arrhythmic induce the torsades de pointes type of ventricular arrhythmia much more easily in females rather than males.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing age has been shown to reduce the use of invasive therapies for ACS, despite the fact that these offer survival benefit at all ages . It is important that comorbidities are taken into account when determining a course of treatment for elderly patients because they may influence vulnerability to adverse drug reactions . There is also an ethical question underlying the decision to intervene (which considers patient choice and beneficence) and it has been acknowledged that physicians may be reluctant to apply therapies to patients with advanced noncardiac comorbidities on the principle of “primum nil nocere” .…”
Section: Discussionmentioning
confidence: 99%
“…Due to uncertainties around the benefits of the invasive interventions, despite their higher risk of adverse clinical outcomes following ACS, older patients may often be managed with more conservative strategies compared with younger patients 19. Although there is evidence to suggest that adherence to guideline-recommended therapy is associated with a decrease in mortality,20 the management of ACS in older age is challenging.…”
Section: Discussionmentioning
confidence: 99%